Practical application of IOT and its implications on the existing software - Israa Sadu; Zahraa A. Jaaz; Haider Hadi Abbas; Haider Abdulshaheed (IAES Indonesia Section, 2020)
The data management from end-to-end level is done by cloud-assisted IOT for its users and they keep a goal in increasing their number of users with the course of time. From saving the infiltration of data from both internal and external threats to the system, IOT is the best-proposed method used for securing the database. Connecting objects/individuals with the Internet via safe interaction is the main objective of IOT. It can assemble all the hardware devices that are designed to store data for an individual or an organization. The associated applications and the way in which it can be deployed in the present organization in order to optimize the current working system. This paper focuses on providing an overall systematic secured data sharing portal that is devoid of threats from internal as well as external entities. By using CIBPRE data encryption a major security reform is introduced by IOT in storing and sharing of data on a regular basis.